Attitudes of Young Adult athletes towards E-Learning and Playing Digital Games for Learning Sports - Tan, Cetin (Mashhad Univ Med Sciences, 2022)
Background: This study aimed at investigating the attitudes of young adults towards e-learning an playing digital games for learning sports. Method: The research group consisted of 189 (77 female, 112 male) young volunteered athletes in the province of Elazig, turkey. A Personal Information Form, Attitude Scale Towards E-Learning in Sports and the Digital Gaming Attitude Scale (DOOTO) were implemented to assess the attitudes of the athletes towards playing digital games with e-learning in sports. Results: The findings revealed that the attitudes of the research sample towards e-learning in sports and playing digital games differed significantly according to their gender, and there was no significant difference in neither of the scales according to the years of exerience in sports and the type of their sport (individual and team sports) (p>0.05). Furthermore, the young adults' attitudes towards e-learning in sports and playing digital games were inversely correlated (R=-.047; R2=.002; p<0.05) Conclusion: In general, a weak negative relationship was found between young adults' attitudes towards e-learning in sports and playing digital games.
Keywords: Digital Gaming; E-Learning; Youth